Strategi Manajemen Perubahan dalam Meningkatkan Disiplin Perguruan Tinggi - Aisyah Fitri Pasaribu; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
Change is something that often happens by itself without realizing it. The purpose of change is so that the organization does not become static but remains dynamic in the face of the times, technological advances and in the field of health services is to increase patient awareness of quality services. Higher education is one form of organization or container where there is an agent of changes that will bring big changes to society. The method used in the application of this research is qualitative-based research. The type of research used is a literature study.